Web-based Development: Smart Blood Bank Management System - Azhar, Nur Maryam Sufiah; Firkhan Ali Hamid Ali (Applied Information Technology And Computer Science, 2022)
Smart Blood Bank Management System is a web-based system developed to help blood bank staff to manage the donor and recipient record. The current system used by the blood bank is a manual system in which the blood bank staff need to register donor and patient manually by filling their details in paper form. With the manual system, there are issues in managing the donor and patient records and there is no centralized database of the donors and recipients. This system allows staff to manage the donor and recipient information. It also accepts registration for people who intend to become a donor. The blood bank staff are able to search for the donor and request blood through this system for the recipient. The development of this system is the Waterfall model methodology which includes six phases namely requirement analysis, system design, implementation, testing, and maintenance. The software used are Visual Studio code and the database used is phpMyAdmin. This system consists of several modules which are login, donor management, blood donation, recipient management, handed over and user. This system is expected to help blood bank staff in managing donor and recipient information.